Efficacy of laser coagulation with a wave length of 0.57 microns in tumours of the iris and iridociliary zone (preliminary studies) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Tumours of the iris and iridociliary zone make from 20 up to 40% of all tumours of the vascular tract. Combined methods of organ-preserving treatment of neoplasms include laser coagulation (LC). Efficacy is achieved due to difference in distribution by the depth of absorbed energy depending on the wave length used. Now lasers are used in dark blue and infrared spectrum of radiation. Radiation of the yellow spectrum with X= 0.57 microns was not used in treatment of neoplasm of the iris and iridociliary zone.Purpose of the study. To increase efficacy of the organ-preserving treatment of tumours of the iris and iridociliary zone by using laser radiation of the yellow spectrum.Material and methods. LC was made in 10patients (10 eyes) with a neoplasm of the iris and iridociliary zone, mean age was 46.6 years old. 6 eyes had pigment-free, 4 — pigmented tumour of the iris and iridociliary zone. Localization of the tumours was in the lower-internal and lower-external quadrants. The sizes of the tumours varied from 2.9 to 24 mm2, and by height they were from 0.7 to 2.8 mm. Laser coagulation was carried out in the yellow range of the spectrum of radiation on the device "Supra" (X= 0.57 microns) of the firm "Ophthalas". The capacity of laser radiation varied from 80 mWt up to 450mWt, diameter of the spot was from 50 up to 200 microns, duration of the impulse from 0.1 up to 0.15sec depending on the degree of pigmentation and prominence in the anterior chamber. The course of treatment consisted of 1-3 sessions with an interval of 1—2 days. Repeated courses were made in 3 month.Results. All patients had regress of the neoplasms after 2—5 courses of laser co-agulation, both in the area and on height. It is noted that the larger the tumour in the area and height, the more significant was its reduction after the first course of laser coagulation.Conclusions. Laser coagulation in the yellow spectrum of radiation with X= 0.57microns of neoplasms of the iris and iridociliary is an effective method of treatment and can be alternative for others used in ophthalmology of lasers. Efficacy is andespecially noted in presence of neogenic vessels in the tumour tissues, irreversible obliteration of their walls with the minimal damage of the surrounding tissues takes place during the moment of their coagulation.
Keywords: tumors of the iris and iridociliary zone; laser coagulation in yellow spectrum